2017
DOI: 10.1002/hed.24760
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and prognosis in patients with head and neck cancer

Abstract: Being underweight at diagnosis was an independent, adverse prognostic factor, whereas being overweight conferred better prognosis. BMI in early adulthood was not associated strongly with head and neck cancer outcomes. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1226-1233, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 40 publications
5
74
1
Order By: Relevance
“…[8][9][10][11] Albergotti et al conducted a retrospective review of 300 patients with HPV positive oropharyngeal HNSCC and found that patients with a BMI less than 25 kg/m 2 had significantly shorter overall and disease-specific survival than their overweight counterparts. [13][14][15] The prevalence of sarcopenia varies based on a number of factors, including race, sex, and BMI. [13][14][15] The prevalence of sarcopenia varies based on a number of factors, including race, sex, and BMI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10][11] Albergotti et al conducted a retrospective review of 300 patients with HPV positive oropharyngeal HNSCC and found that patients with a BMI less than 25 kg/m 2 had significantly shorter overall and disease-specific survival than their overweight counterparts. [13][14][15] The prevalence of sarcopenia varies based on a number of factors, including race, sex, and BMI. [13][14][15] The prevalence of sarcopenia varies based on a number of factors, including race, sex, and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…24 Sarcopenia, however, may be a mediating factor for these findings, as studies suggest that sarcopenia may be associated with poor cancer survival. 13,14,25 Prevalence has been shown to be higher among normal-weight adults (40%) compared to obese adults (8%). 13,14,25 Prevalence has been shown to be higher among normal-weight adults (40%) compared to obese adults (8%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiation dose may impact both weight loss and gastrostomy tube placement and, although this was analyzed in the current study, most patients who were treated with primary radiation received >60 Gy, thereby limiting our ability to analyze this variable. This study was not designed to evaluate disease‐specific outcomes but previous studies have examined the impact of baseline body mass index and peri‐treatment weight loss in the prognosis of head and neck cancer, yielding mixed results suggesting that depletion of skeletal muscle and low body mass index may be prognostic of poorer treatment outcomes …”
Section: Discussionmentioning
confidence: 99%